Pengaruh Bauran Pemasaran Terhadap Keputusan Konsumen Dalam Pembelian Produk Tahu (Studi Kasus: UMKM Rumah Tah Kabupaten Bangka Barat) - Khairunnisa, Tasya; yulia, yulia; Atmaja, Eddy Jajang Jaya (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2023)
Bangka Belitung Province has a lot of potential in developing soybean-based industries, especially tofu and tempeh. One of the businesses that process soybeans into tofu products at Rumah Tahu MSMEs. The number of competitors in the tofu production business and consumers who are increasingly critical in making purchases have caused the Rumah Tahu MSMEs to be able to compete with products offered by similar industries. So with this study, the researchers aimed to analyze the effect of product, price, place, and promotion on consumer decisions in purchasing tofu products at the Rumah Tahu MSMEs and analyze the most dominant factors in influencing consumer decisions in purchasing tofu products at Rumah Tahu MSMEs. This research was conducted from May to July 2022 at Rumah Tahu MSMEs. The research method used in this study is the case study method, the types of data used are primary and secondary data. The sampling method uses the accidental method with several respondents of 100 people. The data analysis method used multiple linear regression analysis. The results showed that the product, price, place, and promotion variables simultaneously have a real influence on the purchasing decision of Tofu Products at Rumah Tahu MSMEs. The product is the variable that has the highest or dominant effect on the purchase decision of Tofu Products at Rumah Tahu MSMEs at a value of 0.280.